FEATURES OF ABSORPTION OF NONPOLAR HYDROCARBONS BY THE STRATIFIED SILICATES IN PRESENCE OF WATER - ZADVERNIUK, G.; KADOSHNIKOV, V.; ZLOBENKO, B. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The sorbtion peculiarities of nonpolar hydrocarbons by disperse layered silicates in the presence of water are considered. It is shown that size of clay minerals particles and their nature are principal factors determining nonpolar hydrocarbons sorption. The mechanism of nonpolar hydrocarbons sorption by clays in the presence of water is proposed.